Campus-wide network of Bukidnon State College - Victoria, Dante S. (Animo Repository, 2001)
This thesis designs a Campus-wide Network architecture and specifies appropriate Academic and Administrative Management Information Systems to run on the network and support administrative and academic computing needs of Bukidnon State College. The study uses the systems approach in planning a new data communication network. In the systems approach, all influences and constraints are identified and evaluated in terms of their impact on the network design. Whether the network achieves success or just marginal utilization may be determined before a single piece of software or hardware is ordered. There are Ten Steps involved in the Network Design (Fitz 1997). Typically, the design of a network infrastructure must conform to the Information System Plan (ISP) of the organization. In the case of Bukidnon State College there is no particular information system plan, so the proponent considered the Institutional Development Plan for 1999-2009 which is also dubbed as Vision 2009 as the basis of his design. The proponent conducted a thorough analysis and assessment of the needs and problems of the different services in BSC aside from the considerations in Vision 2009. Interviews were conducted using the Critical Success Factor (CSF) method to all the key officials of BSC and examined documents to know exactly the needs and problems. Information flows were generated to illustrate the exchange of information between these offices.